Madonna : Bawdy and Soul - Faith, Karlene (Book collections on Project MUSE., 1997)
How do bad girls get away with it? How did Madonna, subject of public outcry for her controversial performances and her book Sex, become a superstar of pop culture and a role model for teenage girls? Why now, as star of Evita and a new mother, is she becoming a mainstream hero? Karlene Faith says that Madonna signifies the times we live in. We are, in a sense, all responsible for who Madonna is. As fans, moral critics, media journalists, or university scholars, we mediate what she means to our society. And Madonna, as a shrewd career woman, has known how to exploit our attentions with her multiple talents. Her representation of sexual practices and values has not taken place in a political or social vacuum. She has counted on our readiness to witness the smashing of cultural taboos. Feminist reactions to Madonna have been divided. In her early career Madonna was a teenage role model, applauded as a liberated sex crusader. Later, she raised eyebrows by portraying cynical sex with multiple partners across identity boundaries and by capitalizing on sadomasochistic imagery. Madonna, Bawdy & Soul is a celebration and critical analysis of Madonna from a feminist perspective. It will, like Madonna, provoke controversy among fans, critics, and scholars. The book includes a comprehensive listing of songs, videos, tours, films, stage roles, and Internet sites.